Cyber security using modern technologies artificial intelligence, blockchain and quantum cryptography - Pal, Om; Kumar, Vinod; Khan, Rijwan 1981-; Alam, Bashir; Alam, Mansaf (CRC Press, 2024)
"The main objective of this book is to introduces cyber security using modern technologies like Artificial Intelligence, Quantum Cryptography and Blockchain. The book provides in-depth coverage of important concepts related to cyber security. Beginning with an introduction to Quantum Computing, Post-Quantum Digital Signatures and Artificial Intelligence for cyber security of modern networks and it also covers various cyber-attacks and the defence measures, strategies and techniques that need to be followed to combat them, the book goes on to explore several crucial topics such as security of Advanced Metering Infrastructure in Smart Grids, key management protocols, Network Forensic, Intrusion Detection Using Machine Learning, Cloud computing security risk assessment model and framework, Cyber-Physical Energy Systems Security, Biometric Random Key Generator using Deep Neural Network and Encrypted Network Traffic Classification. Additionally, the book provides new techniques to handle the modern threats with more intelligence. It also includes some modern techniques for cyber security such as blockchain for modern security, quantum cryptography, forensic tools etc. Additionally, it provides a comprehensive survey of cutting-edge research on cybersecurity of modern networks, giving the reader a general overview of the field. It also provides interdisciplinary solutions to protect modern networks from any type of attack or manipulation. The new protocols discussed in the book thoroughly examine the constraints of network including computation, communication and storage cost constraints, etc and verifies the protocols both theoretically and experimentally. Written in a clear and comprehensive manner, the book would prove extremely helpful to readers. This unique and comprehensive solution for cyber security of modern networks will greatly benefit researchers, graduate students and engineers in the fields of cryptography and network security"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on July 11, 2023)
Keywords: Computer security -- Technological innovations; Sécurité informatique; Innovations; COMPUTERS / Networking / Security; COMPUTERS / Security / General